2010
DOI: 10.1111/j.1365-246x.2009.04439.x
|View full text |Cite
|
Sign up to set email alerts
|

Seismoelectric response of heavy oil reservoirs: theory and numerical modelling

Abstract: International audienceWe consider a linear poroelastic material filled with a linear viscoelastic solvent like wet heavy oils (oil as opposed to water or brines is wetting the surfaces of the pores). We extend the electrokinetic theory in the frequency domain accounting for the relaxation effects associated with resonance of the viscoelastic fluid. The fluid is described by a generalized Maxwell rheology with a distribution of relaxation times given by a Cole–Cole distribution. We use the assumption that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(59 citation statements)
references
References 53 publications
0
55
0
1
Order By: Relevance
“…Moreover, seismograms and electrograms at the observation site correlated well with each other [10,[15][16][17]. Theoretical and observational studies indicated that there were linear relations between the electric field and seismic velocity [10] or acceleration [17], with the coefficient (transfer function) depending on the kinetic property on the site.…”
Section: Coseismic Changesmentioning
confidence: 91%
See 4 more Smart Citations
“…Moreover, seismograms and electrograms at the observation site correlated well with each other [10,[15][16][17]. Theoretical and observational studies indicated that there were linear relations between the electric field and seismic velocity [10] or acceleration [17], with the coefficient (transfer function) depending on the kinetic property on the site.…”
Section: Coseismic Changesmentioning
confidence: 91%
“…from the ordinary coseismic variation moving with the seismic wave as recorded and studied so far [9,10,12,[14][15][16][17][18][19][20][21][22][23]. This is the first report of the detection of this kind of electric variation, that is, correlation with the seismic wave starting from the beginning of fault rupture, in our long history of electric field measurement by using a borehole antenna.…”
Section: Coseismic Changesmentioning
confidence: 91%
See 3 more Smart Citations